Increased risk of acute stress disorder and post-traumatic stress disorder in children and adolescents with autism spectrum disorder: a nation-wide cohort study in Taiwan - Li, Sung-Tao; Chien, Wu-Chien; Chung, Chi-Hsiang; Tzeng, Nian-Sheng (Frontiers in Psychiatry, 2024)
Introduction Children and adolescents with autism spectrum disorder (ASD) may be particularly vulnerable to the impact of traumatic events, yet the association between ASD and the risk of developing acute stress disorder and post-traumatic stress disorder (PTSD) remains uncertain. This study aims to investigate this association, addressing the gap in large-scale evidence on the subject. Methods Conducted as a retrospective and matched cohort study, data was sourced from the National Health Insurance Research Database (NHIRD) in Taiwan, spanning from January 1, 2000, to December 31, 2015. The study included patients aged 18 years or under newly diagnosed with ASD (n=15,200) and compared them with a matched control group (n=45,600). The Cox proportional regression model was employed to assess the risk of acute stress disorder and PTSD. Results Over the 15-year follow-up period, a total of 132 participants developed either acute stress disorder or PTSD. Among them, 105 cases (0.691% or 64.90 per 100,000 person-years) were in the ASD group, while 27 cases (0.059% or 5.38 per 100,000 person-years) were in the control group. The adjusted hazard ratio for the ASD group was significantly higher compared to the control group (25.661 with 95% CI = 15.913-41.232; P < .001). Discussion This study provides compelling evidence that individuals with ASD face an elevated risk of developing acute stress disorder and PTSD. The findings underscore the importance of clinicians recognizing and addressing this vulnerability in ASD individuals exposed to traumatic events. This emphasizes the need for heightened attention to the risk of PTSD and acute stress disorder in the ASD population.